The Financial Distress, Profitability, and Leverage as Antecedents of Audit Delay: An Empirical Study of the Food and Beverage Subsector - Al Farisi, Salman; Anjarwati, Sri (Dinasti Publisher, 2024)
This research aims to find out whether every year audit delays are affected by Financial distress, Profitability, and Leverage. The sample came from the Indonesia Stock Exchange (IDX) by collecting data and then using the Secondary Variable Quantitative Method and data tabulating with the SPSS application. The results will prove whether there is a decrease or increase in the accuracy of the length of time for completing audit reporting during the 2018-2022 period. The results of this study have practical implications for investors to look at audit delays as measured by Financial Distress, Profitability and Leverage. The researcher describes the importance of company measurement to find out how long the auditing report takes obtained from Financial Distress, Profitability and Leverage